Anatomical characteristics and physycal properties of wood of Caesalpinia gaumeri Greenm in Dzan, Yucatan - Interián-Ku, Víctor Manuel; Borja de la Rosa, María Amparo; Valdez-Hernández, Juan Ignacio; García-Moya, Edmundo; Romero-Manzanares, Angélica; Vaquera-Huerta, Humberto (Instituto de Ecología, A.C., 2016)
Caesalpinia gaumeri Greenm is a highly prized species for construction of houses and poles in the Mayan region of Yucatan. In order to contribute to technological knowledge of its attributes and suggest potential uses of wood, were described its anatomical features and physical properties. This work was conducted in four trees in a tropical deciduous forest of Yucatan. It was found that the wood is dark brown color in the heartwood and chestnut in the sapwood, wire is cross, pronounced veining, texture and brightness are average, diffuse porosity; the elements of vessel have simple perforation plates, small pits and inclusions; the rays are uniseriate and biseriate, extremely low and thin; the axial parenchyma is aliform and confluent; fiber medium and cellular wall extremely thick; heavy density and for volumetric contraction as medium; there is no clear transition between early and late wood. By the anatomic characteristic (rays extremely low, thin and abundant, fiber medium and cellular wall extremely thick and inclusions) and physical properties such as heavy density, the wood of C. gaumeri can be used in the development of ties, poles, staves, and crafts. The wire cross and rhomboidal crystal of the wood limits the use in carpentry.